Metode Dakwah Salafi Terhadap Pemerintah Studi Pada Akun Salam TV - Salma Sahari Harahap; Sholeh Fikri; Mohd. Rafiq (Journal of Mandalika Literature, 2024)
Abstract: The purpose of this research is to analyze the da'wah message broadcast by Salam TV account on Instagram media and analyze the attitude of the salafi group towards the government. The research method used in this research is descriptive qualitative with a content analysis approach using observation, interview, and documentation techniques. The data sources in this study are the Salam TV account manager and the content material of Salam TV's da'wah messages. The results of this study found that from the total number of posts, namely 4,477 Salam TV posts, there was no da'wah material criticizing the government and controversial da'wah messages and debates between Salafi and non-Salafi groups. The Salafi group emphasizes that jihad against the government is by delivering gentle da'wah and wise advice and praying for the government without committing acts of violence, hate speech and propaganda. This study also found that the da'wah message conveyed by Salam TV was Akidah, Sharia and Akhlak material.